O'Reilly Software Architecture Conference--London, UK 2018. (O'Reilly Media, 2018)
"SACON London 2018 was four days of guidance, exploration, and discovery on how to become--and remain--the best software architect you can possibly be. Featuring presentations by some of the world's top software architects, systems engineers, data architects, application architects, and DevOps pros, the conference focused on the tools, techniques, and leadership skills required to succeed in the evolving discipline of software architecture. This video compilation contains the best of SACON London 2018's technical sessions, tutorials, and keynotes with hours of material to explore and absorb at your own pace."--Resource description page